2016
DOI: 10.1038/srep32002
|View full text |Cite
|
Sign up to set email alerts
|

Altered Fecal Microbiota Correlates with Liver Biochemistry in Nonobese Patients with Non-alcoholic Fatty Liver Disease

Abstract: Increasing evidence suggests a role of intestinal dysbiosis in obesity and non-alcoholic fatty liver disease (NAFLD). But it remains unknown in nonobese NAFLD. This prospective, cross-sectional study sought to characterize differences in fecal microbiota between nonobese adult individuals with and without NAFLD and their potential association with metabolic markers of disease progression. A total of 126 nonobese subjects were enrolled: 43 NAFLD and 83 healthy controls (HC). The microbial community was profiled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
296
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(325 citation statements)
references
References 60 publications
21
296
4
4
Order By: Relevance
“…However, studies have demonstrated contradictory findings in the relative abundance of Ruminococcus , Prevotella , and Bifidobacterium . Only one study has evaluated the gut microbiota in non-obese adults and found a decrease in Lactobacillus 15 , contrary to findings in obese NAFL.…”
Section: Human Gut Microbiome Profiles In Clinical Phenotypes Of Naflmentioning
confidence: 77%
See 2 more Smart Citations
“…However, studies have demonstrated contradictory findings in the relative abundance of Ruminococcus , Prevotella , and Bifidobacterium . Only one study has evaluated the gut microbiota in non-obese adults and found a decrease in Lactobacillus 15 , contrary to findings in obese NAFL.…”
Section: Human Gut Microbiome Profiles In Clinical Phenotypes Of Naflmentioning
confidence: 77%
“…In NAFL, comparison groups included healthy controls 9,8,10,11,15,16,18,23 and obese controls 21 . In NASH, comparison groups included healthy controls 9,10,12,13,18,19 , obese controls 7 , and NAFL 24,16 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that fecal samples from colon cancer patients had less bacterial diversity compared with samples from healthy individuals and a lower amount of bacterial diversity in the gut may indicate a lack of balance in the complex bacterial population30. Findings also showed that the non-obese patients with nonalcoholic fatty liver disease were characterized by a decrease in gut microbial diversity31. As shown in our data, a significant decrease in the Simpson index (alpha diversity) was only observed in STZ-HFD male mice relative to controls (Supplementary Table S1), which may be a reason why the male mice had a higher risk of developing HCC relative to females.…”
Section: Discussionmentioning
confidence: 97%
“…Adipose tissue releases cytokines to increase inflammation and fibrosis. Gut microbiota is also believed to play a role in the development of NASH via alterations in the BA pool level and composition (Jiang et al, 2015; Liu et al, 2016b; Mei et al, 2015; Wang et al, 2016). Recently, vitamin D deficiency has been proposed as another possible factor as mice fed a high fat diet (HFD) exhibited increased steatosis and hepatic ballooning when coupled with a vitamin D deficiency (Kong et al, 2014).…”
Section: Nafld and Nashmentioning
confidence: 99%